Russia's Theatrical Past : Court Entertainment in the Seventeenth Century - Jensen, Claudia Rae; Waugh, Daniel Clarke; Shamin, S. M.; Maier, Ingrid (Book collections on Project MUSE., 2021)
"In the 17th century, only Moscow's elite had access to the magical, vibrant world of the theater. In Russia's Theatrical Past, Claudia Jensen, Ingrid Maier, and Stepan Shamin, with Daniel C. Waugh, mine Russian archival sources to document the musical history of these productions, originally available only in court venues for the privileged. Using such sources as European newspapers, diplomats' reports, foreign travel accounts, witness accounts, and payment records, they also uncover unique aspects of local culture and politics at the time. Focusing on Northern European and Ukrainian Orthodox musical and theatrical traditions, the authors explore the concept of intertheater, which describes transmissions between performing traditions, and reveal how the Muscovite court's interest in theater and other entertainment was strongly influenced by diplomatic contacts. Russia's Theatrical Past, made possible by an international research collaborative, offers fresh insight into how and why Russians went to such great efforts to rapidly develop court theater in the 17th century"--